2001 Director's report of research in Kansas - Kansas State University. Agricultural Experiment Station (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
This report contains the title, author, and publication information for manuscripts published by station scientists. It also contains a list of the research projects that were active during that period and a financial statement for the fiscal year.
DRR 1
Keywords: Kansas; Agricultural Experiment Station; Research; Publications; Finances; Projects